A Private Key Encryption Scheme based on Amicable Number with User defined Cipher Block Sequencing Techniques - Das, R; Dutta, S (International Journal of Computer Sciences and Engineering, 2025)
Same secret key is used for encryption and decryption in Private Key cryptography. Many of the existing private key cryptography systems lacking their security as distribution of the private-key through public communication channel without interpretation is very hard to achieve. So here our focus is on the secret procedure which retrieves secret value used for encryption from the private-key rather than securing the actual private-key value. The secret value is being derived by taking the first or second item from Nth pair of Amicable number set. Where N is a user defined positive integer in the range of (1<=N<=1024). The counting of Nth pair is being started from a user defined base value towards its forward or backward direction. We impose another level of security by implementing some user defined sequence for positioning encrypted characters block wise in cipher text file. Thus an attempt is made to increase the security in great extant.